2021
DOI: 10.1136/oemed-2020-106955
|View full text |Cite
|
Sign up to set email alerts
|

Line managers’ hiring intentions regarding people with mental health problems: a cross-sectional study on workplace stigma

Abstract: ObjectivesStigma may negatively affect line managers’ intention to hire people with mental health problems (MHP). This study aims to evaluate line managers’ knowledge and attitudes concerning job applicants with MHP, and to assess which factors are associated with the intention (not) to hire an applicant with MHP.MethodsA sample of Dutch line managers (N=670) filled out a questionnaire on their knowledge, attitudes and experiences concerning applicants/employees with MHP. Descriptive analyses and multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 35 publications
(51 reference statements)
1
43
0
Order By: Relevance
“…Apparently, workers with mental illness have a negative reputation. This was also found in a representative study of 670 Dutch line managers, where 40% indicated they were concerned that hiring a worker with mental illness would negatively affect the workplace atmosphere [7]. Finally, future research should also make clear if the findings are generalizable to other countries, or rather specific to the Dutch context and culture.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Apparently, workers with mental illness have a negative reputation. This was also found in a representative study of 670 Dutch line managers, where 40% indicated they were concerned that hiring a worker with mental illness would negatively affect the workplace atmosphere [7]. Finally, future research should also make clear if the findings are generalizable to other countries, or rather specific to the Dutch context and culture.…”
Section: Discussionmentioning
confidence: 64%
“…Also other studies that were not particularly related to the workplace showed that disclosure can lead to acceptance and support [5], and, after completing the Coming Out Proud program, decreased self-stigma and diminished depression [6]. Nevertheless, disclosure can also be a barrier as it can lead to adverse employment outcomes due to stigma and discrimination, such as problems obtaining a job [1,[7][8][9][10], job loss [8,11], limited advancement opportunities [8,12], and harassment at work [13,14]. Also outside the workplace mental illness disclosure can lead to increased self-stigma, shame, harm and discrimination [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous systematic reviews in this area are lacking [8]. One of the suggested factors is that employers and other stakeholders in the work environment often hold negative attitudes towards people with disabilities, which decreases the chances of these people to be hired or supported at work [12][13][14][15][16]. Many people with health problems experience a disclosure dilemma [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…That autonomy might be more challenging to stimulate among employees with CMHP, may be because lack of control is a common manifestation of CMHP ( van der Klink and van Dijk, 2003 ). Due to stigma ( Brouwers et al, 2020 ) or lack of skills ( Janssens et al, 2021 ), supervisors and OHPs easily tend to take over control, while our study shows the importance of experiencing a sense of autonomy in the SAW process. We recommended OHPs and supervisors to stimulate the autonomy of employees and to address their capacities, by (1) encouraging active participation, (2) asking the right questions, (3) listening to their needs, and (4) supporting SAW as much as possible in order to prevent negative work outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…As most individuals affected by CMHP are employed and actually working, this phase of staying at work needs more attention ( OECD, 2012 ; Danielsson et al, 2017 ). Interestingly, nearly 40% of a representative panel of Dutch employers does not know how to help employees with CMHP in the workplace ( Janssens et al, 2021 ). One explanation may be the course of CMHP, in which symptoms appear through implicit or ambiguous signals, usually developing stealthily and slowly.…”
Section: Introductionmentioning
confidence: 99%